Control over future payouts and willingness to pay for insurance: Experimental evidence from Kenyan farmers - Kramer, Berber; Waweru, Carol; Malacarne, Jonathan G. (2023)
The Kenyan economy relies heavily on its agricultural sector. Agriculture contributes 22.4 percent of the country’s GDP, with a majority of the producers being smallholder farmers (KNBS, 2022). This leaves both the economy and the farmers who make up the economic base facing significant risk. Shock events in the recent past underscore this truth. Notably, Kenya experienced significant drought events in 2008-2011 (MOALF, 2021), 2016-2017 (Uhe et al., 2018), and 2020-2022 (FAO, 2021). Such shocks have immediate and lasting effects on farmer well-being (Rosenzweig and Binswanger, 1993; Carter, 1997; Morduch, 1995; Hoddinott, 2006; Janzen and Carter, 2019; Malacarne and Paul, 2022), underscoring the pressing need to strengthen the resilience of smallholder farmers. The increased incidence of drought has made it even more crucial that farmers have tools to transfer the risks they face to financial markets. Financial inclusion (e.g. bank account ownership, access to formal credit markets, access to insurance markets, mobile money coverage) among vulnerable rural populations, however, is often low (Lotto, 2022). Innovations in the design and provision of financial technologies have sought to make tools more accessible to smallholder farmers for whom existing products were not available or were prohibitively expensive. These efforts often make use of information and communications technologies to reduce the cost of offering products and to extend their reach into more distant communities (Benami and Carter, 2021).